Dampak Globalisasi dan Digitalisasi Terhadap Partisipasi Kewarganegaraan di Era Modern - Dies L. Tobing; Gracia Feby Yeski Sitepu; Hana Tresia Sidabutar; Dewi Putri Batubara; Puji Chairunisa; Satya Nofryanti N (Universitas 17 Agustus 1945, 2024)
This research aims to analyze the impact of globalization and digitalization on civic participation in the modern era. Globalization and digitalization have changed various aspects of life, including the way citizens participate in political and social processes. This research uses a literature study method by reviewing various relevant literature, such as scientific journals, books and research reports, to understand how developments in information and communication technology (ICT), as well as global connectedness, influence patterns of civic participation. The research results show that globalization has expanded access to information and increased political awareness at the global level, while digitalization has made it easier for citizens to interact with governments and communities through digital platforms. However, this research also found challenges in the form of the digital divide, disinformation, and uneven engagement across various groups in society. Thus, this research provides insight into the opportunities and challenges in promoting inclusive civic participation in the digital era.